Local Government Strategies for Enhancing Community Sanitation: A Study of the Geser Si Jahat Program - Mochamad Faizal Rizki; Fabya Budi Luthfiana (Universitas Sebelas Maret, 2025)
There are 2.5 billion people in the world who lack access to proper sanitation, and the health impacts of Open Defecation (ODF), such as diarrhea, can cause death. In Bekasi City, only nine out of 56 sub-districts have an open defecation-free (ODF) status. The Local Government, through the Bekasi City Health Office, in collaboration with USAID IUWASH PLUS, formed the GeserSi Jahat program. Although studies on community sanitation programs are common, few have focused on governance innovations to improve community sanitation in urban areas. Through a case study, this study explores how Bekasi City's governance innovations improve sanitation quality. Data were collected by interviewing government actors, Non-Governmental Organizations (NGOs), and local communities; observing program implementation; andanalyzing policy documents, mass media articles, and archival records. The results showed that visionary leadership, trustworthiness, and stakeholder support influence proactive leadership. Civil society strongly influences bottom-up collective demands, represents common interests, and resolves conflicts by revitalizing sanitation forums. Technical management innovation occurs inplanning, implementation, and supervision. Spatial participation realizes coordinated communication, opens equal opportunities across genders, and utilizes the media. This study implies that improving community sanitation quality requires the involvement of stakeholders. Applying a constructivist paradigm it provides insights into how government programs are perceived and adapted at the community level, enriching public administration and governance studies with context-specific knowledge that emphasizes local cultural and social dynamics.